Wild card - Silver, Elsie (Silver, Elsie. Rose Hill series, 2025)
"Sebastian Rousseau is a grumpy, hot-as-hell fire pilot who is too damn good with his hands. It's the perfect combination. But unfortunately for Gwen, he's also her ex-boyfriend's dad. A chance meetingbrought them together, and a missed connection has kept them apart.One year later, a stroke of fate has them living under the same roof, which makes everything between them downright messy. Because evenafter all this time, he's still the man Gwen thinks about when she falls asleep. The one she can't get over no matter how hard she tries"--